Isolation and Identification of Antiplasmodial Compound from Methanol Extract of Calophyllum bicolor P. F. Steven - Abbas, Jamilah; Hanafi, Muhammad; Artanti, Nina; Sundowo, Andini; Minarti, Minarti; Asih, Puji Budi Setia; Syafrudin, Din (BRIN, 2015)
Calophyllum bicolor (Clusiacea) is a big tree from Indonesian rain forest in Palangkaraya, Central Kalimantan. Calophyllum or bintagor is one of many sources of natural bioactive compounds that can be used in the fields of health and pharmaceuticals. The aim of this research was to explore the antiplasmodial activity of methanol extract of Calophyllum bicolor P.F. Steven against Plasmodium falciparum. The methanol extract was purified by colomn chromatography system, hexane – ethyl acetate was used as solvent with increasing polarity. One pure compound was obtained and was elucidated based on the 1H-&13C-NMR and 2D-NMR, [COSY, HMBC and HMQC] data and the isolated compound was identified as xanthone. Methanol extract showed antiplasmodial activity growth inhibition against P. falciparum with IC50 5.2 ppm and the new 5-methoxy trapezifolixanthone compound have maximum inhibition at concentration 0.11 nMol.